Pengaruh Pelatihan Balut Bidai Terhadap Kemampuan Penatalaksanaan Cedera Ekstremitas Atas Pada Remaja Di MA Al-Ittihadiyah Pangkalan Masyhur Medan - Huwaina Af’idah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Splinting training aims to improve everyone's ability to perform emergency care. The purpose of this study was to analyze the extent to which splinting training influences the ability to manage upper extremity injuries in adolescents using the splinting simulation method. This study was a quantitative study using a one-group pretest-posttest design with a sample of 40 adolescent medical students using a purposive sampling approach. Data were analyzed using the T-test. The results of this study showed that there was a significant difference in the skill level of the simulation group between pre and post (p <0.005). So it was concluded that splinting training using direct simulation can improve the ability to manage upper extremity injuries. Therefore, it is hoped that training using this simulation method can be used for all topics, learning types, and every domain; cognitive, affective, psychomotor and interpersonal.